Selection of the optimal maintenance organization for specific purpose devices - Radonjić Vojkan; Đukić Slobodan; Jovanović Danko; Ćirić Milenko; Petrović Saša (Serbian Journal of Electrical Engineering, 2014)
This paper is a result of a broader study, oriented to optimization of maintenance process for special purpose devices and presents the selection of optimal maintenance variant for selected specific purposes device, using the method of analytic hierarchy process, with assumed model of device usage. This paper formalizes the decision process, decision-makers subjectivism boils down to an acceptable level, impruves optimization approach for solving the problems in hierarchical systems, and encourages training in the improvement of decision makers in solving problems of multi character.